Targeted genomic profiling of acral melanoma - Yeh, Iwei; Reuss, David; Deimling, Andreas von (Journal of the National Cancer Institute, 2019)
AbstractBackground. Acral melanoma is a rare type of melanoma that affects world populations irrespective of skin color and has worse survival than other cutan